AUDITOR EXPERIENCE & SKEPTICISM AS MODERATORS INFLUENCING AUDIT QUALITY - Sofian Sofian; Rafael Danendra Reswara; Marcella Salim (Kesatuan Press, 2026)
The complexity of operating environments faced by businesses has further highlighted audit quality, particularly following financial reporting failures that raise concerns about auditor competence and independence. This study examines the relationships among auditors’ competence, independence, and audit quality, with experience and skepticism as moderating variables. This research used a quantitative research approach; data were collected via structured questionnaires distributed via convenience sampling to 125 practicing auditors working at Public Accounting Firms in Surabaya city, and analyzed using regression-based models to assess both direct and interaction effects among the variables. The findings reveal that auditor competence and independence positively influence audit quality. Experience and skepticism fail to moderate auditor competence and audit quality, indicating that competence already reflects the essential professional attributes required to conduct standardized audits. In contrast, auditor experience strengthens the effect of auditor independence on audit quality by enabling auditors to translate independence into effective audit behavior. Skepticism does not serve as a moderating mechanism between independence and audit quality, as it is institutionalized primarily through audit standards. In conclusion, while competence and independence are fundamental drivers of audit quality, auditor experience plays a critical role in enhancing the practical effectiveness of auditor independence.